Protection of Aluminum Foils against Environmental Corrosion with Graphene-Based Coatings - Paterakis, George; Anagnostopoulos, George; Sygellou, Labrini; Galiotis, Costas (Journal of Coating Science and Technology, 2021)
Commercial aluminum foils were coated by graphene oxide, and its functionalized derivatives and the corrosion performance of the coated specimens were examined in acidic conditions (lithium perchlorate and sulfuric acid). Electrochemical experiments have shown that all graphene oxide-coated specimens provided up to 96% corrosion inhibition efficiency with a corresponding lower corrosion rate compared to the bare aluminum foil. Our results clearly show that graphene-related materials offer viable alternatives for the protection of aluminum, and this opens up a number of possibilities for its use in a number of commercial applications.